Perspectives on fiscal federalism - Bird, Richard M. (Richard Miller), 1938-; Vaillancourt, François (WBI learning resources series., 2006)
This book addresses a variety of issues relating to intergovernmental finance and the provision and financing of local services including budgeting and financial management, the institutional framework for the conduct of intergovernmental relations, appropriate methods of service delivery in metropolitan agglomerations and remote rural areas, local government enterprises, user charges, property taxes, income and value-added taxes, natural resource taxes, and local business taxes. Throughout, the authors draw on experience both in Canada and in other decentralized countries and consider to varying extents the special problems facing Russia and other large transitional economies.